2009
DOI: 10.1007/s00586-009-1236-x
|View full text |Cite
|
Sign up to set email alerts
|

Dural lesions in lumbar disc herniation surgery: incidence, risk factors, and outcome

Abstract: In lumbar disc herniation surgery, dural lesions seem to be the most common complication today. Studies on incidence of and outcome after a dural lesion are mainly based on retrospective studies. In a prospective study within the framework of the Swedish Spine Register, 4,173 patients operated on for lumbar disc herniation were evaluated using pre-and 1-year postoperative protocols and complication registration. Mean patient age was 41 (18-81) years and 53% of the patients were male. 93% of the operations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 16 publications
(19 reference statements)
2
28
1
Order By: Relevance
“…The operation safety is the most important factor, but with the increase in lumbar surgery, the complication rate increases accordingly. Several studies have reported on complication rates in various types of patients undergoing operative treatment in the lumbar region [3,15,23]. Major complications of lumbar surgery include blood loss, dural tear, hematoma, deep vein thrombosis, wound infection, seroma, stress ulcer, abdominal distension, urinary retention, and pulmonary embolism [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…The operation safety is the most important factor, but with the increase in lumbar surgery, the complication rate increases accordingly. Several studies have reported on complication rates in various types of patients undergoing operative treatment in the lumbar region [3,15,23]. Major complications of lumbar surgery include blood loss, dural tear, hematoma, deep vein thrombosis, wound infection, seroma, stress ulcer, abdominal distension, urinary retention, and pulmonary embolism [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…Incidence figures for dural lesions in disc surgeries seem to be in the region of 2-6% [13,16,20] with previous surgery being a strong predictor of the complication. In spinal stenosis surgery higher figures should be expected to be encountered due to the wider exposure of the dural sac and to the difficulties created by ligamentous hypertrophy and osteophytes on the facet joints in decompression especially afflicting the nerve roots but also the central cauda.…”
Section: Discussionmentioning
confidence: 99%
“…The one by Strömqvist [47] reports a prospective study from the Swedish Spine Register, dealing with 4,173 patients operated upon for a disc herniation, of whom 2.7% had tears. Although those patients who had dural tears tended to have had previous surgery, the fact that they had a tear did not have any negative implications in the long-term outcome for the patient at 1 year.…”
Section: Disc Herniationmentioning
confidence: 99%